Tunga penetrans Acquired while Traveling in Africa - Eileen M Proctor (Canadian Journal of Infectious Diseases)
Three cases of tungiasis acquired in the course of travel are briefly described, and the biology of the jigger flea, Tunga penetrans, is reviewed.